Effects of breakfast with different calorigenic amounts on blood glucose, insulin and glucagon levels - 黄素霞 傅运兴 王慧铭 GIANGSylvia (Journal of Zhejiang University. Science, 2003)
This study was aimed to investigate the relationship between breakfast and serum glucose, insulin and glueagon concentrations in order to establish a model breakfast appropriate for Chinese. Twenty-four vol-unteers were randomly assigned to four study groups: high carbohydrate breakfast, high fat and protein break-fast, the typical breakfast and fasting. Each subject had serum and urine samples collected while fasting andat 1,2 and 3.5 hours following the meal. The concentration of serum glucose, insulin and glucagon was mea-sured. The levels of serum glucose in group A, B and C differed significantly at 1 and 2 hour after meal com-pared to those at fasting ( P < 0.05) . The serum glucose in group A increased insignificantly after meal. The serum insulin levels were in group A, B and C significant different compared with control group( P < 0.05) .Those peaked at 1 hour after meal ,with group C rising the furthest. Compared with the fasting group, the se-rum glueagons rose and maintained the increase after breakfast in group A, B and C (P < 0.05).The data suggested that various diets with different ealorigenie amounts increased hormone concentration to various extents. We found that a breakfast rich in carbohydrates could maintain proper blood glucose level.